El barrio de Santiago en el centro histórico de Mérida. Del garbo al deterioro y a la ulterior revitalización - Dávila Valdés, Claudia; López Santillán, Ricardo; Jouault, Samuel (El Colegio de México A.C., 2020)
This text diachronically addresses (in the 20th and 21st centuries) what we regard as an important socio-territorial process. It seeks to analyze the transformations of 19 blocks in the Santiago neighborhood, in the historic center of the city of Mérida, Yucatán. To this end, we consider elements of change related to the physical state of the built heritage, its use, the type of residents, as well as other aspects that touch on sociocultural, economic and political aspects. From a logic replicated on a global scale, albeit always with local specificities, we discuss the existence of a gentrification process in the study area.